(7.3)2 + 9.1 divided by (8.7 - 6.1)im not very good with math that much sorry !!
2 answers:
Answer:
18.1
Step-by-step explanation:
(7.3)2+9.1 / (8.7-6.1)
PEMDAS
Paranthesis first so: 7.3 x 2 = 14.6 , 8.7 - 6.1 = 2.6
So the equation becomes 14.6 + 9.1 / 2.6
Division next since there are no exponents or multiplication: 9.1 / 2.6 = 3.5
Equation becomes 14.6 + 3.5
Addition next: 14.6 + 3.5 = <u>18.1</u>
Answer:
i think you put the 7.3X2+9.1 then divided it by 8.7 -6.1
Step-by-step explanation:
let me see if i can help you
You might be interested in
Answer:
4(2x+6)=32 x= 1
Step-by-step explanation:
multiply 4 to 2x and 6= (8x+24)=32
then subtract 24 from 32 = 8
then divide 8 from both sides
8x/8=8/8
x=1
Answer:
(4, 3)
Step-by-step explanation:
x = (-2 + 10)/2 = 4
y = (3+3)/2 = 3
(4,3)
Answer:48
Step-by-step explanation:3×16=48
Answer:
52 mph
Step-by-step explanation:
think of it this way:
miles/hour
so 364/7 is 52